Using of the Electron Microscope to Evaluate the Tool Wear for a Selected Cutting Insert - Naprstkova, Natasa; Sramhauser, Karel; Cais, Jaromir; Stancekova, Dana (Manufacturing Technology Journal, 2018)
Using of cutting inserts is currently a normal part of the manufacturing process. The article deals with analysis of tool wear after machining at one selected cutting insert. Evaluation of this insert was made by electron microscopy. There was used SEM and EDS analysis. For this purpose was used scanning electron microscope Tescan Vega 3 and EDS analyzer Bruker 16 which is part of this microscope. These analysis can provide a good picture of the structure and construction of inserts, their composition and for situation on the insert after machining. This may assist in finding suitable cutting conditions. As experimental material the hardened steel class 16MnCr5 according to EN 10027-1 has been machining. SEM images of final tool wear of the cutting insert were recorded. The reason was to map the tool wear state after machining using electron microscopy to give a better view of the situation. These analyzes were performed in other experiments performed at the Faculty of Mechanical Engineering at Jan Evangelista Purkyne University in Usti nad Labem.
Keywords: Cutting Insert; SEM; EDS; Tool Wear